The Concept of the Common Good in Catholic Philosophy - Markus Huber; Clara Schmid; Fabian Meier (Philosophy Global: International Journal of Christian and Catholic Philosophy, 2024)
Focusing on the Catholic understanding of the common good, this article examines its philosophical underpinnings and practical implications. The study analyzes the writings of papal encyclicals and classical Catholic thinkers, highlighting how the concept shapes discussions on social justice, economic policy, and global solidarity.